A novel mutation in TANGO2 gene associated with recurrent muscle weakness with rhabdomyolysis , metabolic encephalopathy and cardiac arrhythmia: a case report - Zahra Alkhawaja; Salwa M. Alkhalifi; Sahar Tulbah; Zuhair Al-hassnan (Journal of Biochemical and Clinical Genetics)
Background TANGO2 depletion was found to cause clinically recognizable multi-organ involvement disorder in pediatrics with episodic muscle weakness recurrent rhabdomyolysis, intellectual disability, metabolic encephalomyopathic crises and cardiac arrhythmia. TANGO2 deficiency is also referred to as "metabolic encephalomyopathic crises, recurrent, with rhabdomyolysis, cardiac arrhythmias, and neurodegeneration" (MECRCN) in OMIM. * 616830